Autobiographical Voices Race, Gender, Self-Portraiture (Cornell University Press, 2018)
Adopting a boldly innovative approach to women's autobiographical writing, Françoise Lionnet here examines the rhetoric of self-portraiture in works by authors who are bilingual or multilingual or of mixed races or cultures. Autobiographical Voices offers incisive readings of texts by Zora Neale Hurston, Maya Angelou, Marie Cardinal, Maryse Condé, Marie-Thérèse Humbert, Augustine, and Nietzsche.